Steric and Electronic Factors Influence Regio‐isomeric Thiazole Formations Between Substituted Benzothioamides and Ethyl Bromopyruvate. (9th December 2013) - Liang, Jun; Soucy, Valerie Dorman; Tusi, Vickie; Liu, Yanzhou; Zhang, Birong; Lai, Yingjie; Magnuson, Steve; Zhu, Bingyan; Wang, Fangdao; Gu, Jinghao; Zhang, Qingfen; Wu, Yuan; et al.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>